Application of Femtosecond Laser in Anterior Segment Surgery - Sang Beom Han; Yu-Chi Liu; Karim Mohamed-Noriega; Jodhbir S. Mehta (Journal of Ophthalmology)
Femtosecond laser (FSL) is a near-infrared laser that can create reliable and reproducible tissue cutting with minimal damage to adjacent tissue. As the laser can also create incisions with various orientations, depths, and shapes, it is expected to be a useful tool for anterior segment surgery, such as cornea, refractive, and cataract surgery. In this review, the authors will introduce the application of FSL in various anterior segment surgeries and discuss the results of studies regarding the efficacy and safety of FSL in cornea, refractive, and cataract surgery. Experimental studies regarding the potential use of FSL will also be introduced. The studies discussed in this review suggest that FSL may be a useful tool for improving the prognosis and safety of surgeries of the anterior segment.